Hepatoprotective Potential and Histological Studies of Effects of Celosia Argentea L. on Paracetamol-Induced Liver Damage - Ogunlana O. O., Bello, O. A., Dokunmu T. M. Oyelade I. F.; & Oladele F. W., Ezekiel O. M. (Covenant Journal of Physical and Life Sciences, 2018)
Celosia argentea L. is a common vegetable known to possess anti-oxidative and other therapeutic properties. This study evaluates the hepatoprotective activities and histological effects of aqueous extract of Celosia argentea L. on acetaminophen-induced liver damage in rats, compared to the effects of a standard drug –silymarin. Twenty-five male rats were used in this study. These were divided into five groups of five animals each. Animals in group 1 were given 1ml/kg body weight (b.w) distilled water (control [C]), group 2 were given 100mg/kg b.w silymarin for 4 days plus acetaminophen for 3 days [SL], groups 3 and 4 were given 250 and 500mg/kg b.w aqueous extract of C. argentea for 4 days plus acetaminophen for 3 days (CA1 and CA2, respectively) and group 5 were given 1 ml/kg b.w. distilled water for 4 days and 1g/kg b.w acetaminophen (PCM) for 3 days. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and total bilirubin activities were assessed on day 8, values of mean and standard error were compared at significance level of p < 0.05. Overall, mean ALT, AST and ALP levels in CA2 (21.8 ± 1.4, 84.2 ± 8.2 and 175.9 ± 36.9 U/L, respectively) was lower than PCM group and similar to SL group (37.6 ± 3.9, 97.2 ± 5.2 and 151.1 ± 21.91, respectively, p > 0.05). Mean values in control group were similar to CA2 but significantly lower than PCM and CA1. Total bilirubin was higher but not significantly different compared to C group, suggesting a lack of effect on total bilirubin. C. argentea ameliorates and protects against acetaminophen-induced liver damage in rats, with a comparable effect with silymarin at a dose of 500mg/kg b.w. A regular consumption of the vegetable can play a role in sustaining health and can be used in place of long term therapy in individuals with compromised liver or actively exposed to chemotherapeutic drugs with adverse effects on liver.